Arab EFL learners’ acquisition of verbs of senses - Saeed, Aziz Thabit; Fareh, Shehdeh (Adam Mickiewicz University, 2012)
This study attempts to explore the difficulties that Arab EFL learners of English encounter in the use of five verbs of senses when used as copulas, main verbs, main verbs with a metaphorical use, and as parts of idioms. A questionnaire consisting of three parts was specially designed to elicit the necessary data for this study at the levels of recognition and production. The subjects of the study were 30 randomly selected senior English major university students. The results of the study show that the students encountered tangible difficulties in using the five target verbs. A hierarchy of difficulty was established and the main causes of the problem were identified.